Dlaczego komedia? Rozważania Giorgia Agambena jako próba odpowiedzi - Żak, Miłosz (Zagadnienia Rodzajów Literackich, 2022)
In his text titled Comedy, included in the collection of essays named The End of the Poem, Giorgio Agamben — the famous contemporary Italian philosopher — took up the problem of the ambiguity of Dante Alighieri’s Divine Comedy title. This issue has always been present in Dante studies since the Comedy itself was written. However, Agamben’s essay concerning this topic has not yet been met with interest among researchers of medieval or Italian literature, which seems to be quite significant. In this paper the author critically examines Agamben’s suggestions for interpretation of the title to see if they can broaden the horizon of Dante research. The confrontation of Agamben’s theses with previous concepts — the historical (Giovanni Boccaccio, Benvenuto da Imola) and the contemporary (Erich Auerbach, Amilcare A. Ianucci, Teodolina Barolini) — reveals the originality, but also the controversy of his ideas. The Italian philosopher entangles himself in the philological tradition, pointedly disputing with personages from the exegetical history, but at the same time he expounds his own interpretation. Nevertheless, as the author proves, there is no doubt that Agamben makes a significant contribution to the state of research on the title of the Divine Comedy revealing — among other things — deeply hidden cultural motivations of this academic phenomenon.